Research and Development in Agroforestry in Asia - Tejwani, K.G. (Indian Journal of Agroforestry, 2020)
Agroforestry is a very old and traditional practice adopted by farmers. Surprisingly it is site specific. When there was global hue and cry about the shortage of fuelwood, importance of Agroforestry in farming systems was realized. In this paper, research and achievements in Agroforestry in Asia in past 20 years have been discussed.